Longitudinal shear behaviour in composite slab with profiled steel decking - Ang, Yi Wen (2013)
Composite slabs with profiled sheeting are broadly used in steel framed structures throughout the world. Its shear behaviour is a complex phenomenon to be explored, and hence, experimental and theoretical studies are carried out to investigate its shear strength under imposed flexural loading to evaluate using m-k method, Partial Interaction method and Force Equilibrium method.